2006
DOI: 10.1093/jee/99.3.864
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Repellency, and Transfer of Chlorfenapyr Against Western Subterranean Termites (Isoptera: Rhinotermitidae)

Abstract: Chlorfenapyr is a slow-acting insecticide against western subterranean termite, Reticulitermes hesperus Banks, when applied to sand. The LD50 at day 7 for workers is 29.98 ng per termite and considerably higher than that of chlorpyrifos (14.01), cypermethrin (3.21), and fipronil (0.16). Brief exposures to sand treated with chlorfenapyr resulted in dose-dependent mortality over a broad range of concentrations. Brief 1-h exposures to > or =75 ppm provided >88% kill of termites at day 7. Chlorfenapyr deposits did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…Both hut trials, supported by tunnel tests, indicate that the lower chlorfenapyr dosages (100-250 mg ⁄ m 2 ) are no less effective than higher dosages against A. arabiensis and C. quinquefasciatus. Against termites, the effectiveness of chlorfenapyr as a barrier treatment is largely attributed to its non-repellent toxic activity and to its long half-life which is about one year in soil (Rust & Saran 2006). Against mosquitoes, N'Guessan et al (2007b) observed that chlorfenapyr is non-irritant at low dosages but stimulates take-offs at higher dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Both hut trials, supported by tunnel tests, indicate that the lower chlorfenapyr dosages (100-250 mg ⁄ m 2 ) are no less effective than higher dosages against A. arabiensis and C. quinquefasciatus. Against termites, the effectiveness of chlorfenapyr as a barrier treatment is largely attributed to its non-repellent toxic activity and to its long half-life which is about one year in soil (Rust & Saran 2006). Against mosquitoes, N'Guessan et al (2007b) observed that chlorfenapyr is non-irritant at low dosages but stimulates take-offs at higher dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Observational data from Þeld plots have provided evidence of termite mortality away from the treated soil (Potter andHillery 2002, Kard 2003). Several factors can affect the transfer process: inherent insecticide toxicity and its concentration, substrate type, exposure time of the donor, and time expired after exposure (Shelton and Grace 2003, Rust and Saran 2006, Tsunoda 2006, Saran and Rust 2007. Dissemination of insecticide may be caused by horizontal transmission through contact or social behaviors.…”
Section: Abstract Reticulitermes þPronil Toxicity Transfer Intermentioning
confidence: 99%
“…A study by Spomer et al (2008) revealed that transfer occurs in the Þrst 6 h of donorÐ recipient interaction and is positively affected by temperature. Transfer of Þpronil or chlorfenapyr from R. hesperus-treated termites to naṏve termites can occur by contact (Haagsma 2003, Rust and Saran 2006, Saran and Rust 2007. Tomalski and Vargo (2004) studied the colony-level effect of imidacloprid (another nonrepellent termiticide) on R. flavipes.…”
Section: Abstract Reticulitermes þPronil Toxicity Transfer Intermentioning
confidence: 99%
“…These termiticides are considered to be more effective in controlling termites by killing them some distances away from the treated structures (Potter and Hillery 2002). However, recent studies have shown that the extent of horizontal transfer of termiticide among foragers was limited to 5Ð 6 m from the treated barrier (Osbrink et al 2005, Su 2005, Rust and Saran 2006, Saran and Rust 2007. Thus, the residual amounts and bioavailability of termiticides over time may be the primary factors contributing to the termiticide efÞ-cacy in soil.…”
mentioning
confidence: 99%